Spotlight on Transition in Patients With Inflammatory Bowel Disease: A Systematic Review. Issue 3 (24th August 2019) - Erős, Adrienn; Soós, Alexandra; Hegyi, Péter; Szakács, Zsolt; Erőss, Bálint; Párniczky, Andrea; Mezősi, Emese; Rumbus, Zoltán; Sarlós, Patricia
Abstract: Background: Transition of adolescents from pediatric to adult care is of great importance in the management of inflammatory bowel disease (IBD). Our aim was to review and summarize the currently applied interventions and outcomes related to transition practices in IBD. Methods: A systematic review was performed in accordance with the PRISMA Statement. We searched PubMed, EMBASE, CENTRAL, and Web of Science databases up to February 15, 2019. Controlled studies evaluating adolescents and young adults with IBD participating in structured transition interventions or patient educational programs and single-arm (before-after) studies were included. Several individual, health care, and social outcomes were assessed. The PROSPERO registration number is CRD42019118520. Results: A total of 23 articles were eligible for qualitative synthesis. Eleven studies compared an intervention to a control group, whilst 12 studies were uncontrolled before-after studies. The age of the participants varied from 11 to 25 years. The most common structured transition interventions were joint visits and patient education programs. IBD nurses were operating as nominated transition coordinators in the transition process. Quality of life, patient satisfaction, self-efficacy, disease-specific knowledge, adherence rate, and nonattendance rate at outpatient clinic were identified as main health care transition outcomes besides disease-related outcomes. Despite the various study designs and methodological limitations, outcomes improved with the application of structured transition interventions in eleven of the studies. Conclusion: These results facilitate the design of randomized controlled trials along better standards in transitional care in IBD. Abstract : Structured transition interventions and patient education programs may improve health care transition outcomes among patients with IBD. Due to the observed very low quality of evidence, future well-designed trials are warranted.